2016
DOI: 10.1371/journal.pone.0161582
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the NS5 (VPg) Protein of Murine Norovirus Induces a G1/S Phase Arrest

Abstract: Murine norovirus-1 (MNV-1) is known to subvert host cell division inducing an accumulation of cells in the G0/G1 phase, creating conditions where viral replication is favored. This study identified that NS5 (VPg), is capable of inducing cell cycle arrest in the absence of viral replication or other viral proteins in an analogous manner to MNV-1 infection. NS5 expression induced an accumulation of cells in the G0/G1 phase in an asynchronous population by inhibiting progression at the G1/S restriction point. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…PYCR1 leads to cell cycle arrest [104,105]. A similar mechanism has been shown for the murine NoV VPg [106]. It remains unknown if VPg directs cell cycle arrest through PYCR1 downregulation.…”
Section: Discussionsupporting
confidence: 56%
“…PYCR1 leads to cell cycle arrest [104,105]. A similar mechanism has been shown for the murine NoV VPg [106]. It remains unknown if VPg directs cell cycle arrest through PYCR1 downregulation.…”
Section: Discussionsupporting
confidence: 56%
“…Cell cycle modification is an adventitious strategy of viruses to promote replication and transmission(76). MNV has also been shown to induce a G 0 /G 1 cell cycle arrest which is at least partially dependent on the viral protein VPg in RAW cells(19, 77). Davies et al reports Affymetrix data from 18 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that infection of a macrophage cell line with MNV results in a G0/G1 cell cycle arrest, and that expression of MNV viral protein genome-linked (VPg) alone is sufficient to induce the arrest [16,17]. MNV VPg is a multi-functional protein required for several important functions within the cell, including genome replication and viral protein translation.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of Y26 with an alanine (Y26A) prevents the interaction of MNV VPg with viral RNA [18,20]. In the context of the cell cycle, a Y26A mutation has no effect on G0/G1 accumulation, suggesting that the cell cycle arrest does not require attachment of MNV VPg to the viral RNA [16]. A second, well-characterized function of MNV VPg is to recruit host eukaryotic initiation factors (eIFs) for preferential translation of the viral genome during infection [21,22].…”
Section: Introductionmentioning
confidence: 99%